Synthesis, characterization and complexation studies of bis-oxy biphenyl based novel diamides - Raj Rajadurai; Ramar Padmanabhan; Sarkkarai Ananthan (Arabian Journal of Chemistry, 2019)
A series of bis-oxy biphenyl based diamides have been synthesized and characterized from spectral and XRD data. All the diamides form charge-transfer (CT) complex with 7,7,8,8-tetracyanoquinodimethane (TCNQ). Keywords: Diamides, HBTU, Charge transfer complex, TCNQ